Pengaruh Pengajaran Bauran terhadap Hasil Belajar Siswa pada Mata Pelajaran PPKn di SMPN 8 Mataram - Irfanul Furqan; H. M. Ismail; Ahmad Fauzan; Edy Herianto (LP2M STIT Palapa Nusantara, 2022)
This study aims to determine: Is there any effect of applying the blended learning outcomes on Civic Education at SMP Negeri 8 Mataram. This study uses a quantitative approach with a quasi-experimental type with a Nonequivalent Control Group Design. The population in this study is the total number of students in class VIII at SMP Negeri 8 Mataram which consists of 8 classes and the sample uses 2 classes. The data was collected by using observation and test techniques. The test technique was carried out with a pretest and posttest. The data analysis was carried out with a prerequisite test consisting of a normality test and a homogeneity test, and the effect test was carried out by testing the hypothesis using the t test. The results showed that the implementation of the teaching mix was carried out in 4 meetings and adjusted to the basic components of the teaching mix. And there is the application of the application of the mix to student learning outcomes in Civics subjects. It is proven by the results of the t-test at a significance level of 5% where the results are tcount > ttable value (2,6204 > 2,0057).